Examining Retro Merchandise Consumers in Sport: Who Prefers Throwback Merchandise and Why? - Zach Scola; Brian Gordon; Brendan Dwyer (Journal of Applied Sports Management, 2022)
Retro marketing in sport has been relied upon for years. Sport fans see more teams and leagues implement retro marketing and merchandise into marketing plans. Despite this, we have little understanding behind the success of retro marketing in sport. Therefore, this paper sought to gain a better understanding of the demographic characteristics of retro merchandise consumers and to examine the impact of two psychographic factors. Surveys collected from fans of various professional sport teams in the United States (N = 1,509), demonstrated novel findings. In this study retro merchandise was preferred overall, younger fans were more likely to prefer retro merchandise, and household income did not explain much of the preference. Most telling was that nostalgic proneness significantly and positively predicted a retro preference. The implications from this study should guide marketers in their usage of retro merchandise and marketing practices and lead to future practical research on the topic.
Keywords: retro marketing; nostalgia; branding; merchandise